Legal protection of Tasak Telu as an indicative product of Karo origin from the perspective of Law 20 of 2016 in Sari Laba Village, Biru-Biru sub-district, Deli Serdang District - Gurning, Fretty Luciana Malau; Chairunisa, Puji; Sitepu, Gracia Feby Yeski; Siahaan, Parlaungan Gabriel; PA, Reh Bungana Br (The International Journal of Politics and Sociology Research, 2023)
The problem to be discussed in this research is the form of legal protection for Tasak Telu as an indicative product of Karo origin; The government's efforts to provide legal protection for Tasak Telu. Geographical indications in their development can be beneficial. This is because legal protection can be enforced for regional specialty products which can increase added value and encourage a region to improve superior products. Indication of Origin products as intellectual property assets seen from the regional context certainly have their own differences and characteristics in each region. Indication of Origin is one of the Intellectual Property regimes that regulates the marking of a product so that it is clear that the special character of the product is essentially influenced by its place of origin. As is the case in Sari Laba Village, Biru-Biru District, Deli Serdang Regency, there is Tasak Telu food which is an Indicated product of Karo Origin. This food has the potential to be an asset for economic commodities and to improve community welfare in Sari Laba Village if managed well. This research uses a Normative-Empirical research method with data collection techniques through interviews with respondents at the research location in Sari Laba Village, Biru- Biru District, Deli Serdang Regency. The data collection technique is data reduction, data display, and data verification. The research results show that Law Number 20 of 2016 provides a strong legal basis to protect Tasak Telu as an indicative product of Karo origin. However, the implementation of this law still faces several challenges, such as a lack of understanding on the part of producers and stakeholders regarding the rights and obligations related to geographical indications. Therefore, efforts need to be made to increase awareness and understanding of this legal protection, as well as develop cooperation between related parties to ensure the effective protection of Tasak Telu.